(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This paper explores the development tendencies of online insurance and insurance systems in the digital age. It examines key trends such as seamless online experiences, personalized offerings, digital claims processing, and Insurtech innovations. The study also highlights regulatory considerations and outlines future outlooks for the industry. By understanding these emerging trends, insurers can effectively leverage technology to enhance customer satisfaction, streamline operations, and stay competitive in an evolving market.